Princeless. Volume 6, Make yourself. Part two - Whitley, Jeremy (Action Lab Comics, 2017)
Bedelia's long-sought reunion with her mother may turn out to be much less momentous than she had hoped for. Meanwhile, Adrienne's attempts to rescue the twins are interrupted by a dragon attack on the Dwarven village--the Dragon Slayers leap to action, but confusions abounds when it is revealed the dangerous dragon is in fact Sparky's mother.